The Future of the Past: Technology and the Study of Early Modernity. - Rose, Colin (Sixteenth Century Journal)
The author comments on the use of technology in the study of early modern history. He mentions the ongoing digitization of archives which enables access by more scholars and students, the new kinds of analyses that can be done with digital data, and the use of spatial analysis software such as was used in the DECIMA Project studying the census of Florence, Italy.